ٚدسحعخص اسرث اَر أ اٍ٘ه اىشماج ذٗطثٞقاذٔ فٜ تٞد اى اَه ت اَىٞشٝا Investment of ZakÉt Funds and its Applications by Baitulmal in Malaysia Pelaburan Harta Zakat dan Perlaksanaannya di Baitulmal Malaysia - Awang, Abdul Bari (International Islamic University Malaysia, 2011)
* أعظخر غِخػذ رمغُ ح فٌمٗ ٚأفٛي ح فٌمٗ - و ١ٍش ؼِخسف ح ٌٛكٟ ٚح ؼٌ ٍَٛ حلإ غٔخ ١ٔش، ح ٌخ ؼِش حلإعلا ١ِش ح ؼٌخ ١ٌّش abdbari@iium.edu.my : خِ ١ٌض ٠خ . ح زٌش ٠ذ حلإ ىٌظشٚ ٟٔ 144 اىرجذٝذ ىذ ا اىخا سٍ ػشز . اىؼذد اىراسغ اٗىؼشزُٗ . 1432 ٓ / 2011 ً كخؿش لٍِش ظٌؤع ١ظ ١٘جش سلخرش ؽشػ ١ش طظىْٛ ِٓ ػ خٍّء رخ ؾٌش ٠ؼش ٚخزخسء فٟ حلالظقخد طظٛ ٌٝ حلإؽشحف ػ ٍٝ أػ خّي ر ١ض ح خٌّي - ٚ ِٕٙخ حعظؼ خّس أ ِٛحي ح ضٌوخس - ٚ طشؽ ١ذ خِّسعخط ،ٗ ح ػٍُ رؤْ ز٘ح ح ٌٙخص ح ٌُّٙ فٟ ظِٕٛ شِ ح ؾٌٕخه ح خٌّ ٌٟ حلإعلا ِٟ فٟ خِ ١ٌض ٠خ ٠فظمذ ا ٌٝ ؼًِ زٖ٘ ح ٌٙ ١جش ح ؼٌ ١ٍّش . اىني اَخ الأساسٞح : أ ِٛحي ح ضٌوخس ، حلاعظؼ خّس، فخثل أ ِٛحي ح ضٌوخس، أف خٕف غِظلمٟ ح ضٌوخس، ح ٢سحء ح فٌمٙ ١ش، ادحسس ػ ١ٍّخص حلاعظؼ خّس، ح شٌلخرش ح ؾٌشػ ١ش . Abstract The investment of zakÉt funds is one of the many new issues facing Islamic jurisprudence in our time. It has been debated and studied by scholars individually and under the banner of Islamic juristic academies. Some basic juristic views have crystallized around it that are a matter of consensus, while differences of opinion still persist regarding some of its aspects and ramifications. The present article attempts to specifically examine the legality of investing the surplus of zakÉt funds after distribution has been made to the categories (aÎnÉf) entitled to those funds as specified by the Qur’an. This is done with reference to the Malaysian experience of Baitulmal which is under the auspices of the Council of Islamic Religious Affairs in the Federal Territory of Kuala Lumpur, in attempt to assess and evaluate its performance from both the juristic and economic points of view. The study has adopted an analytical and comparative approach to examine, contrast, and compare the views of contemporary Muslim jurists on the investment of zakÉt funds. It has also analyzed the official reports issued by Baitulmal regarding its investment operations in respect of the abovementioned funds. The study has been able to scrutinize and verify the views of contemporary jurists on the issue at hand and to highlight the modes and ways undertaken by Baitulmal in investing zakÉt funds in areas that can benefit the eight categories entitled to zakÉt. The study has also put into strong relief the immediate need to set up a Sharī‛ah supervisory body comprising both Sharī‛ah scholars and economic experts to monitor and advise on the operations carried out by Baitulmal, including investment of zakÉt funds; such a body is already long overdue. Keywords: Keywords: zakÉt funds, investment, zakÉt funds surplus, categories of zakÉt recipients, juristic views, management of investment operations, Sharī‛ah supervision.